Pengaruh Corporate Social Responsibility terhadap Kinerja Keuangan Perusahaan di Sektor Energi dengan Risiko sebagai Mediator - Risyona, Vania; Tannia, Tannia; Bajuadji, Doddy Surja (Business Management Journal, 2025)
The development of financial performance analysis, sustainable finance, and risk management in Indonesia has put pressure on companies to improve their social responsibility. This study aims to look at the correlation between CSR (Corporate Social Responsibility), with financial performance, and risk as a mediator in companies in the IDX energy sector whose business activities are closely related to the environment. This research is descriptive quantitative with the help of SMART-PLS 4.0.9.9 as a statistical tool to process panel data from 27 samples of companies in the IDX energy sector during 2021-2023 with a total of 81 observations. KLD (Kinder, Lydenberg, and Domini's) Measurement is used as a proxy for CSR. Meanwhile, financial performance is measured by 2 approaches, namely accounting based measures and market based measures. The risk variable is measured based on the standard deviation of the daily stock return. This study found that CSR has a significant relationship with the company's financial performance. However, there is no significant relationship between CSR and risk, risk and financial performance, and risk as a mediating variable, in companies in the energy sector on the IDX 2021-2023. The results of this study indicate that CSR can contribute to improving the company's financial performance, so stakeholders can pay attention to this aspect. The limited research time covering 3 years of observation will limit data coverage and not reflect long-term trends. In addition, the proxies used have limitations in interpreting the results as a whole. Future research is expected to develop this study in reviewing the influence of both the energy sector and other sectors.